Adding Corticosteroids to the Pudendal Nerve block for Pudendal Neuralgia: A Randomised, Double-blind, Controlled Trial. Issue 11 (November 2016) - Labat, J. J.; Riant, T.; Lassaux, A.; Rioult, B.; Rabischong, B.; Khalfallah, M.; Volteau, C.; Leroi, A.-M.; Ploteaua, S.
Abstract : (Abstracted from BJOG 2016; DOI: 10.1111/1471-0528.14222) Management of pudendal neuralgia (PN) is often not evidence based. The practice of adding corticosteroids to a nerve block in patients with PN is widespread and largely based on a few studies suggesting that corticosteroids may prolong the effect of a local anesthetic.